Managing meteorological risk through expected shortfall - Silvana Stefani; Gleda Kutrolli; Enrico Moretto; Sergei Kulakov (Risks, 2020)
This paper focuses on weather derivatives as efficient risk management instruments and proposes a more advanced approach for their pricing. An "hybrid" contract is introduced, combining insurance properties, specifically tailored for the region under study and introducing Value-at-Risk (VaR) and Expected Shortfall (ES) as appropriate measures for the strike price. The numerical results show that VaR and ES are both efficient ways for managing the so-called Tail Risk; further, being ES more conservative than VaR and due to its subadditivity property, it can be seen that seasonal contracts are generally better off than monthly contracts in reducing global risk.
Keywords: 330; climate change; temperature; risk hedging; Value-at-Risk; Expected Shortfall; portfolio diversification